Correlation between Respiratory Muscle Strength and the Global Physical Activity Questionnaire among Monks at Rangsit City Municipality: a Preliminary Study - Buranapuntalug, Sasipa; Yuenyongchaiwat, Kornnaong (Journal of Health Science of Thailand, 2017)
Physical activity and respiratory muscle strength are one factor that affect cardiopulmonary system. However, few studies have been reported physical activity and respiratory muscle strength among monks. In addition, no study examined the relationship between physical activity and respiratory muscle strength in monks. The objective of this study was to assess the correlations between physical activity and inspiratory and expiratory muscles strength among monks at Rangsit City Municipality. It was conducted as a cross sectional study. The samples were thirty-one monks who completed self-administrated Global Physical Activity Questionnaire (GPAQ) and their inspiratory and expiratory muscles strength were measured. It was found that an averaged physical activity among the monks was 6,040.81 Metabolic Equivalent (MET)-min * week-1 which was at high level of physical activity. The average inspiratory and expiratory muscles strength was 88.39 cmH2O and 101.32 cmH2O, respectively. The correlations between physical activity level and both inspiratory and expiratory muscles strength were observed. In conclusion, there was a significant association between level of physical activity and respiratory muscle strength. Therefore, promotion of respiratory muscle strength and encouraging physical activity should be emphasized in order to improve the general health.